PROFESSIONAL ETHICS OF A PSYCHOLOGIST AS A SUBJECT OF RESEARCH IN A LEGAL SCIENCES - Oleshchenko, Veronika; Нolovko, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to find out the place of professional ethics of a psychologist in the system of legal science research, by studying the relationship between the ethical principles of a psychologist, moral norms and legal norms. Research methods: the methodological basis of the study are general methods of thinking, functional, systemic, structural and synergetic methods. Results: the subject of research of professional ethics of psychologist and legal science is analyzed, the interrelation between the main categories of science of professional ethics of psychologist and legal science in a broad sense is established. The main aspects of the influence of the legal field (legal norms) on the professional activity of a psychologist and the formation of ethical and moral principles of a psychologist are highlighted. Discussion: it is established that the subject of study of professional ethics of a psychologist is public relations, special ethical issues that arise in the professional activities of a psychologist, as well as a set of moral imperatives and ethical principles. The relationship between the rules of law and the principles of professional ethics of a psychologist in the course of professional activity has been studied. The purpose of the ethical principles of the psychologist is the consolidation of universal values as the main reference point and as the main limit of practical activity. Among the ethical principles of the psychologist, the main ones are: respect and protection of human rights, respect for the individual, responsibility, honesty and openness in relations with the person, professional competence, purposefulness in achieving the goal of helping people. The foundation for the formation of ethical principles of the psychologist are universal moral principles, among which are: respect for the individual, respect for human rights and freedoms, friendliness, desire to work in the interests of the client and for his benefit, the principle of humanity, confidentiality. All these moral norms are reflected in human rights standards, international and national, expressed and enshrined in law. Of course, morality and law are closely intertwined. In the context of this area of research, we can conclude that the rules of morality are the essence and content, and the rules of law are their shell. Therefore, of course, the professional ethics of the psychologist as a science of ethical and moral principles of the psychologist, can be the subject of research in the legal sciences in the context of the study of ethical and moral principles in the legal field.